Frequency and clinical features of radiographic head injury caused by inpatient falls: a single-centre retrospective cohort study - Hiroshi Okamoto; Toru Hashimoto; Fumiaki Tokioka; Akiko Shiotsu (BMJ Open)
Objectives The lack of clear criteria makes it difficult for clinicians to determine which patients should be imaged after an inpatient fall. This study identified the clinical characteristics of patients who required a head CT scan following an inpatient fall.Design This was a retrospective cohort study conducted from January 2016 to December 2018. We obtained the data from our safety surveillance database, which record all cases of inpatient falls in our hospital.Setting Single-centre, tertiary, secondary care hospital.Participants We included all consecutive patients who claimed to have fallen and bruised their heads as well as patients who were confirmed to have a bruise on the head but were unavailable to be interviewed about the fall.Primary and secondary outcome measures The primary outcome was radiographic head injury revealed on head CT after a fall.Results Overall, 834 adult patients (662 confirmed and 172 suspected cases) were included. The median age was 76 years, and 62% were men. Patients with radiographic head injury were more likely to have a lower platelet count, consciousness disturbance and new vomiting episodes compared with those without radiographic head injury (all p<0.05). The use of anticoagulants or antiplatelets was not different between patients with and without radiographic head injury. Among the 15 (1.8%) patients with a radiographic head injury, 13 with intracranial haemorrhage had at least one of the following characteristics: received anticoagulant or antiplatelet agents, platelet count of <2.0×109/L, consciousness disturbance or new vomiting episodes. There were no deaths among patients with radiographic head injuries.Conclusions The incidence of radiographic head injury due to falls in adult inpatients with suspected or confirmed head injuries was 1.8%. Only patients with risk factors had radiographic head injuries, which might help reduce the number of unnecessary CT scans in inpatient falls.Trial registration number Study protocol (Kurashiki Central Hospital, Medical ethical committee. IRB no. 3750).